Auslaufen von Heizöl auf Nachbargrundstück. - (:unkn) unknown (Boorberg, 2001)
Bundesgerichtshof, Urteil. difu
Keywords: Bodenverunreinigung; Schadstoff; Schadenersatz; Haftung; Wasserhaushaltsgesetz; Gemeinde; Umweltschutz; Ölverschmutzung; Heizöl; Gemeindestraße; Nachbargrundstück; Kontamination; Verursacher